Resilience and Robustness of Composite Steel and Precast Concrete Track Slabs Exposed to Train Derailments - Mirza, Olivia; Kaewunruen, Sakdirat (Frontiers in Built Environment, 2018)
Sydney Harbour Bridge (SHB) is an iconic structure constructed in 1923 in Sydney, connecting North Sydney and Sydney CBD. It is a steel-arch structure that caries 8 road lines and 2 rail tracks. Rail tracks of the bridge presently use conventional timber transoms (or sleepers) as track support structure. Replacement of aging and failing timber transoms annually cost public tax money significantly as a result of the high turnover rate of components caused by salt spray, electrolysis, humidity, aggressive dynamic condition and so on. Steel-concrete composite transoms have been found to be a feasible alternative to timber transoms, which enable systems compatibility with the structural configuration of Sydney Harbour Bridge. However, critical literature review on composite transoms reveals that their impact failures due to train derailments have not yet been considered. In fact, the derailment impacts can cause progressive failure to the bridge structure system. This paper therefore investigates the unprecedented impact damage and failure modes of composite transoms during train derailments. The derailment loads was considered in accordance with Australian Bridge Standard AS5100. The train derailment load was simulated using three dimensional non-linear finite element modelling by ABAQUS. The damage and failure behaviour of the precast concrete-steel composite transoms was then analysed. The ductility of composite slabs can be observed from the yielding of both reinforcements and steel sheets during the impact loading. The dynamic finite element analysis is found to be capable of making reasonable predictions by determining the possible failure modes of steel-concrete composite track slabs subjected to impact loads.